2011
DOI: 10.1073/pnas.1019612108
|View full text |Cite
|
Sign up to set email alerts
|

Circadian transcriptional regulation by the posttranslational oscillator without de novo clock gene expression in Synechococcus

Abstract: Circadian rhythms are a fundamental property of most organisms, from cyanobacteria to humans. In the unicellular obligately photoautotrophic cyanobacterium Synechococcus elongatus PCC 7942, essentially all promoter activities are controlled by the KaiABC-based clock under continuous light conditions. When Synechococcus cells are transferred from the light to continuous dark (DD) conditions, the expression of most genes, including the clock genes kaiA and kaiBC, is rapidly down-regulated, whereas the KaiC phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 23 publications
(34 reference statements)
4
48
0
Order By: Relevance
“…strain PCC 6803, a DNA microarray analysis identified ϳ50 significantly rhythmic genes, whereas rhythmic clock gene expression was limited to low-amplitude kaiA expression (29). Moreover, we recently found that in Synechococcus the expression rhythms of only a subset of genes are dampened in the dark, even when de novo kai gene expression is turned off (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…strain PCC 6803, a DNA microarray analysis identified ϳ50 significantly rhythmic genes, whereas rhythmic clock gene expression was limited to low-amplitude kaiA expression (29). Moreover, we recently found that in Synechococcus the expression rhythms of only a subset of genes are dampened in the dark, even when de novo kai gene expression is turned off (9).…”
Section: Resultsmentioning
confidence: 99%
“…This was originally thought to be the core of the circadian oscillation in Synechococcus (6). Although we have demonstrated that the kaiBC expression rhythm is not an essential requirement for circadian regulation (8,9), most previous molecular and physiological studies have successfully used a bioluminescent reporter (luciferase) to monitor the rhythm of the high-amplitude kaiBC promoter activity under LL (10,11). In Synechococcus, KaiA activates the autophosphorylation of KaiC, and this activation is antagonized by KaiB.…”
mentioning
confidence: 88%
“…However, the degree to which the circadian clock and light availability independently affect metabolic events is poorly understood. In S. elongatus, only two studies have investigated the behavior of mutants that lack a functional clock under an LD cycle (21,25). The available studies investigate these effects only over a lightto-dark transition, so currently there is an incomplete understanding of the circadian influence on cellular events over a full 24-h LD cycle.…”
mentioning
confidence: 99%
“…However, the circadian cycling of KaiC phosphorylation persisted when Synechococcus cells were maintained under continuous-dark conditions (DD) in the absence of de novo transcription and translation of the kai clock genes (3). Even during DD, the cyanobacterial clock regulates part of the transcriptional output, dependent on Kai protein-based posttranslational oscillation (PTO) (4). Moreover, the self-sustained oscillation of KaiC phosphorylation was reconstituted in vitro by incubation with Kai proteins and ATP (5).…”
mentioning
confidence: 99%